Budidaya Padi Beras Merah Skala Rumah Tangga Berbasis Usaha Pekarangan - Gusti R. Sadimantara; Muhidin Muhidin; Dewi Nurhayati Yusuf; Dedi Erawan; Gusti Ayu Kade Sutariati; Tresjia Corina Rakian; Waode Nuraida (Vokasi Universitas Halu Oleo, 2022)
Brown rice (Oryza sativa) is a highly nutritious staple food that contains anthocyanins in addition to carbohydrates, fat, protein, fiber, and minerals. Anthocyanins serve as antioxidants, playing a crucial role in plant and human health. Efforts to improve rice production, particularly upland rice production, are always coupled with efforts to increase production of brown rice. The majority of brown rice is produced from upland rice. There has been no effort to manufacture brown rice before today. Therefore, efforts to expand upland rice production with native cultivars are inextricably linked to efforts to boost upland rice output of red rice. Upland rice is brown rice consumed without going through a grinding process or the process of removing the bran and bran from the endosperm of the rice. Rice is only ground into broken rice so that the husk is still attached to the endosperm and has high nutritional value. Strong body immunity and excellent health levels are needed. One of them is by consuming healthy food that is available locally and has become a daily food menu, it only needs to increase production and processing efforts so that it is always healthy. Upland brown rice can be planted as an intercrop to maximize land use for plantation crops, so it has the potential to be developed in Southeast Sulawesi because there is still a lot of unused land or land that has not been used optimally. Therefore, in the context of providing healthy food and functional food based on upland red rice, which farming families can reach, and close to the location of the farmers' livelihoods, it is necessary to increase brown rice production through the introduction of brown rice cultivation technology as a garden plant and also as a family medicinal plant.